Decomposition and drivers of energy intensity in Ghana - Oteng-Abayie, E. F.; Dramani, J. B.; Adusah-Poku, F.; Amanor, K.; Quartey, J. D. (Elsevier, 2024)
Ghana's energy intensity trends point to a high energy use necessary to generate a unit of output. The country has also witnessed massive investment in energy infrastructure geared towards meeting its lower middle-income status and achieving universal access to energy. The logical question is: what is the contribution of the current economic and technical infrastructure level to the country's energy intensity? The current study addresses this question by employing the Logarithmic Mean Divisia Index I (LMDI) to decompose energy intensity in Ghana from 2000 to 2020 to examine its trends and sources. The impact of economic-technical factors on aggregate energy intensity in Ghana is then investigated with the aid of the ARDL estimation technique to unearth potential asymmetric and symmetric effects. The decomposition analysis indicates an oscillating pattern in energy intensity in Ghana promoted by structural effect and labour productivity respectively. The results suggest that renewable energy, rural electrification, and digitisation have a direct and secondary long-run asymmetric effect on aggregate energy intensity with labour productivity and household consumption working as the transmission channels. The study recommends the need for government to pursue clean and eco-friendly practices in its economic development agenda for a meaningful reduction in energy intensity.